Integrasi Etnomatematika Rumah Adat NTT Dalam Pembelajaran Matematika - Balibo, Dionisius Asa; Blegur, Irna K. S.; Dominikus, Wara Sabon (Fraktal : Jurnal Matematika dan Pendidikan Matematika, 2025)
Ethnomathematics is mathematics that grows and develops in the cultural activities of certain communities. This means that mathematics and culture are two things that are interrelated and cannot be separated in people's lives. This research aims to examine the integration of NTT traditional house ethnomathematics in mathematics learning and learning approaches that support learning. The research method used in this research is literature study. The 3 articles used were obtained from the Google Scholar database. The results of this research show that the ethnomathematics activities of NTT traditional houses can be integrated into mathematics learning and a realistic mathematics approach can have an impact in creating active learning that is centered on contextual problems in the environment around students.